Avaliação da qualidade da água de lavagem de filtros e de lodo de decantador após tratamento sequencial por leito de drenagem, flotação por ar dissolvido e filtração - Oliveira, Nilton Fernandes de (2015)
In this study, we evaluated the quality of filter backwash water and sludge decanter Water Bom Jardim Treatment Plant, located in Uberlandia, Minas Gerais, after sequential treatment with drainage bed, flotation and filtration dissolved air, all bench scale. Compounds were evaluated drainage bed effluent three different types of geotextile webs: RT-21, RT-26 and RT-31, and tested three kinds of constituents of the sand grain size filters. The effluent drained, after passage through the drainage bed, passed through the flotation unit dissolved air and then by filtration units. Preliminary tests with crude sample of filter backwash water and sludge decanter, in order to characterize it and evaluate it as its physical, chemical and biological were performed. The geotextile webs used were chosen from results of previous studies, performed with the same type of system. The experiments were divided into stages I and II. In step I were conducted without addition of coagulant or auxiliary experiments on coagulation / flocculation flotation. The samples, after passage through the system, evaluating physical parameters pH, turbidity, true color and apparent color and about the chemical parameters, remaining concentrations of aluminum and iron. Step II The same tests were carried out in the same step I and determination of quality parameters, however, with aluminum sulphate dose of 5, 10 and 15 mg / L in the coagulation / flocculation flotation. Tests conducted in step I showed better performance were performed with the RT-26 blanket in the output of filter 01 with a reduction of 91.8% of the apparent color, 41.4% of true color and 97.6% turbidity. In phase II trials conducted in the best performance was drained with the RT-mat 26 the output of the filter 02 when subjected to a dosage of 15 mg / L aluminum sulfate as a coagulant agent. There was a reduction of 96.4% of the apparent color, 86.2% of true color and 99.6% turbidity. The presented results confirm the efficiency of the system in removing solids present in the water washing of filters and ETA decanter sludge studied and confirmed the capability of using this system as an alternative to disposal or optionally for a new water supply line treated.